2016
DOI: 10.1002/2015jd024090
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant effect on cloud condensation nuclei for two‐component internally mixed aerosols

Abstract: This work presents experimental data on the cloud condensation nuclei (CCN) activity of two‐component mixtures containing surfactants. Nine binary systems were tested combining strong ionic (sodium dodecyl sulfate) and nonionic surfactants (Zonyl FS‐300 and Triton X‐100) with nonsurfactant compounds (glucose, ammonium sulfate, or sodium chloride). Control tests were performed for systems combining organic (glucose) and inorganic compounds (ammonium sulfate or sodium chloride). Results show that CCN activity de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
144
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(158 citation statements)
references
References 151 publications
(250 reference statements)
13
144
0
1
Order By: Relevance
“…This is consistent with a slight dynamic shape factor of 1.01-1.04 of crystallized ammonium sulfate (Biskos et al 2006;Zelenyuk et al 2006). Somewhat larger deviations were seen for sodium chloride, which has a dynamic shape factor of »1.08 in its cubic crystalline form (Zelenyuk et al 2006;Wang et al 2010;Petters and Petters 2016). More strongly shaped crystalline particles may bias viscosity estimates if D c and D uc are not both known.…”
Section: ¡3supporting
confidence: 69%
“…This is consistent with a slight dynamic shape factor of 1.01-1.04 of crystallized ammonium sulfate (Biskos et al 2006;Zelenyuk et al 2006). Somewhat larger deviations were seen for sodium chloride, which has a dynamic shape factor of »1.08 in its cubic crystalline form (Zelenyuk et al 2006;Wang et al 2010;Petters and Petters 2016). More strongly shaped crystalline particles may bias viscosity estimates if D c and D uc are not both known.…”
Section: ¡3supporting
confidence: 69%
“…Aerosols were generated by atomizing the aqueous solutions. Previous work has suggested that incomplete mixing of aerosol components in aqueous solution and/or fractionation of components during atomization can contribute to variability and uncertainty in hygroscopicity measurements for aerosol systems containing surface-active components, particularly for components with low water solubility (Petters and Petters, 2016). However, because PEG is highly water soluble, it is not expected that this was a significant contributor to uncertainty in experimental results.…”
Section: Aerosol Systemsmentioning
confidence: 99%
“…No observable change in the particle flow temperature or humidity was measured after valve switching actions. Glucose was chosen as a reference compound because it is non-volatile at the time scale of DMA transit, its water activity vs. water content relationship is precisely known from isopiestic measurements (Miyajima et al 1983), the water activity vs. water content relationship is essentially independent of temperature (Zamora et al 2011;Christensen and Petters 2012), the variation of glucose growth factors with S H2O is similar to that of GLY allowing measurements to stay within a narrower overall DMA sizing range, and the dried dynamic particle shape factor approaches unity (Suda and Petters 2013;Petters and Petters 2016). The resulting humidigrams reflect the combined hygroscopic growth and evaporation at a fixed temperature vs. S H 2 O .…”
Section: Experimental Scan Strategiesmentioning
confidence: 99%